Re: Submission of technical documents under design services agreement rev.01 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the revised submission of technical documents under design services agreement of BRACU new campus project.